Determinan Kemiskinan di Provinsi Lampung dalam Perspektif Ekonomi Syariah: Peran Pertumbuhan Ekonomi, Upah Minimum dan Indeks Pembangunan Manusia - Ningsih, Retna; Retna; Hilyati Aulia, Hanna; Puspita Sari, Dwi Retno (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of economic growth, minimum wage and the Human Development Index on the number of poor people in Lampung Province. Poverty is a multidimensional issue, not only related to low income but also encompassing aspects of education, health and access to economic resources. High poverty levels can hinder development, making it crucial to understand its determinants more deeply. This research uses a quantitative approach with an associative design and panel data regression analysis. The data used is secondary data from the Central Statistics Agency (BPS) of Lampung Province for the period 2018-2024, covering 15 regencies/cities. Panel data regression combines cross-sectional and time series data, providing more accurate estimates. The technique involves several stages, including selecting the best model among the Common Effect Model, Fixed Effect Model and Random Effect Model through Chow test, Hausman test and Lagrange Multiplier test. The purpose of using panel regression is to determine the influence of independent variables both simultaneously and partially on the number of poor people, as well as to capture the dynamics of poverty changes based on regional and temporal differences. The research results show that, partially, the minimum wage has a significant influence on the number of poor people in Lampung Province. Conversely, economic growth and the Human Development Index do not statistically significant. However, all three variables simultaneously have a significant influence on poverty. These findings imply that increasing the minimum wage directly contributes to reducing poverty, while the influence of economic growth and Human Development Index is indirect or insignificant during the study period. From an Islamic economic perspective, poverty is not merely an economic phenomenon but a matter of social justice (ʿadl) and collective responsibility. The findings of this study can be interpreted within the framework of maqāṣid al-syarīʿah, particularly the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), and wealth (ḥifẓ al-māl), highlighting the importance of fair wage policies and human development as instruments of poverty alleviation in Islamic economic policy.